Serum long noncoding RNA urothelial carcinoma-associated 1: A novel biomarker for diagnosis and prognosis of hepatocellular carcinoma. Issue 1 (January 2018) - Zheng, Zhi-kun; Pang, Cui; Yang, Yang; Duan, Qiong; Zhang, Ju; Liu, Wen-chao
Objective: Long noncoding RNAs (lncRNAs) offer great potential as cancer biomarkers. This study was performed to assess the applicability of serum lncRNA urothelial carcinoma-associated 1 (UCA1) as a diagnostic and/or prognostic biomarker for hepatocellular carcinoma (HCC). Methods: We examined UCA1 expression in serum samples from 105 patients with HCC, 105 patients with benign liver disease (BLD), and 105 healthy volunteers using reverse-transcription polymerase chain reaction and analyzed the relationship between serum UCA1 and clinicopathological parameters of HCC as well as survival. Results: Expression of serum UCA1 was significantly higher in patients with HCC and allowed for discrimination of HCC from BLD and healthy controls. High expression of serum UCA1 was significantly associated with a high tumor grade, large tumor size, positive vascular invasion, and advanced TNM stage. Multivariate analysis revealed that a high serum UCA1 level was an independent unfavorable prognostic factor for HCC. Conclusions: Our results confirm the upregulation of serum UCA1 expression in HCC and indicate its clinical value as a noninvasive biomarker for HCC screening and prognostic prediction.